ANALISIS PENGARUH PENGALAMAN KERJA, DISIPLIN KERJA, DAN TINGKAT PENDIDIKAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN PD. SUMBER MAKMUR PANGKALPINANG - Al Farozi, Ihsan; Ahmad Agin, Arka'a; Miranda, Lona (Jurnal Progresif Manajemen Bisnis, 2018)
The purpose of this study is to examine the effect of work experience, work discipline, and level of education on employee productivity PD. Sumber Makmur Pangkalpinang. The research method used is the purposive sampling method. The research respondents were 30 people with PD. Sumber Makmur Pangkalpinang. The variables used are work experience, work discipline, and level of education as independent variables, and employee productivity as a dependent variable developed according to its own indicators. This research uses quantitative analysis to primary data direct research results in the field. As a tool in the processing of statistical data used SPSS 22 program. The results showed that: First, there is a significant influence of work experience variables on work productivity. This is evidenced by the value of t-count (3.631)> t-table (2.04841). Second, there is a significant influence of the work discipline variables on work productivity. This is evidenced by the value of t-count (3.689)> t-table (2.04841). Third, there is a significant influence of variables Education level on work productivity. This is evidenced by the t-count (4,001)> t-table (2.04841). Fourth, there is a significant influence of variable Work experience, work discipline, and level of education simultaneously to work productivity. This is evidenced by the value Fcount (8,008)> Ftable (3.37). Based on the results of these studies, the researcher concludes that employee productivity PD. Sumber Makmur Pangkalpinang can be improved through Work Experience, Work Discipline, and Education Level.